The anti-cancer effect of Ant-44 (Spermidine-Anthracene Conjugate) via Ornithine decarboxylase activity in K562 cells - Abdul Ghani, Radiah; Phanstiel, Otto; Wallace, Heather M. (2015)
Background Many tumors undergo dysregulation of polyamine homeostasis and up-regulation of ornithine decarboxylase (ODC) activity, which can promote carcinogenesis. The polyamine conjugate has shown promising chemopreventive activity against a range of human tumor cell types, but little is known about the effect of this agent on leukemic cell lines. Here, we investigated whether inhibition of ODC by one of the polyamine anthracene conjugate, Ant 44, could contribute to the anti-cancer effect in human chronic myeloid leukaemic cells, K562.